The Gálvez Family and Spanish Participation In the Independence of the United States of America - Cummins, Light Townsend (Revista Complutense de Historia de América, 2007)
This article examines the role that the Gálvez family played in setting and implementing the policy by which Spain implemented her participation the American Revolution. The members of the Gálvez family played an important role at every stage of Spain’s involvement in the conflict. This essay analyzes the activities of José de Gálvez as Minister of the Indies, his brother Matías de Gálvez as commander in Central America, and Matías’s son, Bernardo de Gálvez, as governor of Louisiana. Their activities also resulted in the beginnings of diplomatic relations between Spain and the United States when José de Gálvez sent Juan de Miralles and Franciso de Rendon to Philadelphia as observers at the Continental Congress. The work of the Gálvez family created a situation that materially assisted the United States and the activities of the family were an important reason why the Revolution resulted in the defeat of Great Britain.